The Effect of Different Fertilizers' Sources on Micronutrients' Content and Sugar Quality of Sugar Beet. Issue 3 (3rd July 2019) - Ahmadpoor Dehkordi, Elahe; Tadayon, Mahmoud Reza; Tadayyon, Ali
Abstract: In order to evaluate the effect of different fertilizers' sources on micronutrients' content and sugar quality of sugar beet, three fertilizers' sources include spent mushroom compost (SMC) (29 t/ha), sheep manure (23 t/ha), chemical fertilizer including zinc sulfate (10 kg/ha), copper sulfate (10 kg/ha), iron sulfate (30 kg/ha), manganese sulfate (15 kg/ha) and no fertilizer (control) were conducted in a randomized complete block design with three replications at Research Farm of Shahrekord University in 2013. The results showed that micronutrients' content in the root, α-amino-N sucrose percentage and sucrose yield were significantly affected by fertilizer treatments. The highest elements' content of Fe (90.39 mg/kg), Zn (39.15 mg/kg), and Cu (18.1 mg/kg) in sugar beet root belonged to SMC treatment. Besides, SMC caused less α-amino-N accumulation in sugar beet compared with sheep manure (1.05 MEq/g). Sucrose percentage was higher in SMC treatment than the sheep manure. Likewise, sucrose percentage revealed a significant positive correlation with micronutrients of zinc, copper, and manganese in sugar beet root. Therefore, it could be concluded that using SMC increases micronutrients' content in the root and at the same time, plays an important role in sugar quality improvement of sugar beet.